Aura of night [large type] - Graham, Heather (Graham, Heather. Krewe of hunters, 2022)
Author Megan Law would like to forget her kidnapping ordeal, but a turn of events convinces her to work with FBI investigator Ragnar Johansen and try to uncover the truth behind the Embracer killings.